Optimization of Spot Welding Performance Through Microcontroller- Solenoid Drive and Ultrasonic Sensing - Aldi Rahman; Surfa Yondri; Riza Widia; Muhardika; Yani Kamisa Putri; Dedi Erawadi; Tri Artono; Muhammad Rizal Syauqii (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2025)
This research discusses the design and testing of an Arduino microcontroller-based spot welder control system with solenoid drive and ultrasonic sensor as the main input. The system is designed to improve efficiency, precision, and consistency of welding results by automating the electrode clamping process as well as voltage regulation according to material specifications. The combination of a relay and voltage regulator module allows the current to be optimally adjusted based on the thickness of the work plate, thereby reducing welding defects. Tests show that the system is capable of detecting objects within 10 cm, and a welding time setting of 3 seconds proves sufficient to produce an optimal weld point. On plates with a thickness of 1.44 mm, the best results were achieved at voltages of 4V and 6V; for thicknesses of 1.8 mm and 2.2 mm, the optimal voltage was 8V. The pressure from the solenoid proved to be sufficient in joining the materials well. These results show that the microcontroller-based welding system is effective in adaptively managing the welding time and voltage, and provides consistent and robust results. These findings support the potential application of the system in smarter and more automated production processes in accordance with industry 4.0 principles.